Meta Analysis of Efficacy and Safety of Moxibustion on Neurogenic Bladder after Spinal Cord Injury - Xueqi HAN; Huirong HUANG; Zhongbiao XIU; Jingling WU; Qinyu LIU; Shaofang MIAO; Xiaona YAN (康复学报)
Objective:To evaluate the efficacy and safety of moxibustion in the treatment of neurogenic bladder (NB) after spinal cord injury (SCI) by Meta analysis, so as to provide evidence-based basis for improving the prognosis of NB after SCI.Methods:Data were searched from the databases of PubMed, Cochrane Library, Web of science, EMbase, OVID, China National Knowledge Infrastructure (CNKI), China Biomedical Literature Database (CBMdisc), Wanfang Database (Wanfang Data) and Chinese Scientific Journal Database (VIP). The patients with NB after SCI were included in the randomized controlled trial (RCT) who were treated with moxibustion at home and abroad. The retrieval time for each database was from the established time to May 31,2019, and the references of related literatures were traced back at the same time. The total effective rate was the primary outcome indicator. Residual urine volume, bladder capacity and bladder pressure were the secondary outcome indicators. Two researchers screened literature, extracted data and evaluated the quality of the literature, and analyzed the data using RevMan 5.3 software. According to the systematic review manual provided by the Cochrane Collaboration Network, continuous variables use mean difference (MD) and 95%confidence interval (CI) as indicators, and binary variables use risk ratio (RR) and 95%CI as indicators. The statistical heterogeneity was judged comprehensively by chi-square (χ2) test and Heterogeneity test (I2test). If P≥0.1 and I2≤50%, a fixed effects model would be used. In contrast, if P<0.1 or I2>50%, a random effects model would be used.Results:A total of 12 Chinese RCT literatures were included. There were 740 subjects, including the experimental group (n=370) and the control group (n=370). The results of Meta analysis showed that the total effective rate of neurogenic bladder after spinal cord injury in the experimental group was higher than that in the control group[RR=1.38, 95%CI (1.25,1.52), P<0.000 01], could reduce the residual urine volume of NB patients after SCI[urodynamic test group: MD=-37.00, 95%CI (-43.48,-30.53), P<0.000 01; B-scan ultrasonography inspection group: MD=-29.88, 95%CI (-36.26,-23.50), P<0.000 01; urethral catheterization group: MD=-33.28, 95%CI (-57.03,-9.53), P=0.006], could increase the bladder capacity of patients with NB after SCI[urodynamic test group: MD=50.73, 95%CI (14.47,87.00), P=0.006; B-scan ultrasonography inspection group: MD=51.07, 95%CI (30.06,72.07), P<0.000 01], and could effectively regulate the bladder pressure of NB patients after SCI[MD=2.03, 95%CI (1.07,3.00), P<0.000 1], and the difference was statistically significant (P<0.05).Conclusion:Moxibustion can effectively reduce bladder residual urine volume, increase bladder capacity and regulate bladder pressure in patients with NB after SCI. It has high clinical efficacy and high safety, but the absolute effect is not exact. It still needs to be further verified by large samples and high-quality randomized controlled trials to provide more reliable evidence-based basis for clinical practice.